Conhecimento e utilização do diamino fluoreto de prata entre cirurgiões-dentistas do estado do Paraná - Koller, Ingrid Biberg (2021)
Dental caries is a disease still considered a global public health problem that, if left untreated, has negative consequences for the overall health and quality of life of individuals, especially children. With reference to disease control/treatment in the context of minimally invasive dentistry, the literature points to a variety of products and interventions for this purpose, such as Atraumatic Restorative Treatment, sealants, fluoride products in their various forms, and also silver diamine fluoride (DFP). This is a promising intervention for the treatment of caries lesions, since it is affordable, easy to apply, safe, painless and can be used in large scale. The attributes make DFP amenable to wide use in public health. Thus, the aim of this cross-sectional study was to identify the knowledge and use of the DFP among dental surgeons in the state of Paraná, Brazil. To this end, in the period from August to October 2021, with intentional sampling, data collection took place through a questionnaire via Google® Forms for 100 professionals, made available through a telephone communication application. The tool had 22 objective questions that dealt with demographic aspects, professional training and use of the material in question. Data were tabulated in Microsoft Excel® and analyzed in SPSS® version 25.0. Student's t test and Chi-square were applied. Values of p < 0.05 were considered a statistically significant difference. Sixty dental surgeons participated (response rate = 60%). Women comprised 91.7% of the total sample and the mean length of training was 15.9 (± 11.7) years. Participants with longer average training time (19.8 ± 1.9 years) claimed to use the DFP more when compared to those who had trained less time (p = 0.01). A statistically significant difference (p = 0.02) was also found regarding the place of work, since those who work in the public service use the material more. A total of 27 (45.0%) were positive about the use of the DFP, however, a diversity of answers regarding knowledge of the use and indications of the DFP was observed. More than 40% of the respondents do not know which is the most indicated concentration of the product, and 77.8% indicate it only for children. Furthermore, 70.4% remove softened tissue before applying the DFP. As for the advantages of the DFP, the bactericidal/cariostatic action was mentioned by 74.1% of the respondents and the fact that there is no need for more invasive interventions (55.6%). There was unanimity when the aesthetic issue was mentioned as the biggest factor limiting the indication of treatment with DFP. It was concluded that the knowledge about the use of DFP among the dentists investigated here is deficient, which reinforces the need for continued education actions and the development of utilization protocols, which may favor the increase of the use of this material.